Age- and Sex-Specific Changes in CMR Feature Tracking-Based Right Atrial and Ventricular Functional Parameters in Healthy Asians - Leng, Shuang; Guo, Jiajun; Tan, Ru-San; Chai, Ping; Teo, Lynette; Fortier, Marielle V.; Gong, Chao; Zhao, Xiaodan; Ong, Ching Ching; Allen, John C.; Ruan, Wen; Koh, Angela S.; et al. (Frontiers in Cardiovascular Medicine, 2021)
Cardiovascular magnetic resonance (CMR) is the reference standard for non-invasive assessment of right-sided heart function. Recent advances in CMR post-processing facilitate quantification of tricuspid annular (TA) dynamics and longitudinal strains of the right ventricle (RV) and right atrium (RA). We aimed to determine age- and sex-specific changes in CMR-derived TA dynamics, and RV and RA functional parameters in healthy Asian adults. We studied 360 healthy subjects aged 21–79 years, with 30 men and 30 women in each of the six age groups. Functional parameters of RV and RA were measured on standard four-chamber cine CMR using fast feature tracking: (1) TA peak velocities (systolic velocity S′, early diastolic velocity E′, late diastolic velocity A′) and TA plane systolic excursion (TAPSE); (2) RV global longitudinal strain (GLS) and strain rates; and (3) RA phasic longitudinal strains and strain rates. S′ and TAPSE exhibited negative correlations with age. RV GLS was significantly higher in females than in males but not associated with age in both sexes. Females had similar E′, lower A′, and higher E′/A′ ratios compared to males. Positive associations of E′ and E′/A′, and negative association of A′ with age were observed in both sexes. Females had higher RA reservoir and conduit strains compared to males. There were significantly negative and positive associations between RA conduit and booster strains, respectively, with age. Age- and sex-specific reference ranges were established, and associations revealed, for fast CMR feature tracking parameters of right heart function in a large normal Asian population.